2008
DOI: 10.1021/jf802671p
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Germinating Rice Seeds

Abstract: A metabolite profiling approach based on gas chromatography-mass spectrometry (GC-MS) was used to investigate time-dependent metabolic changes in the course of the germination of rice. Brown rice kernels were soaked and incubated for a total of 96 h under ambient conditions. Samples taken during the germination process were subjected to an extraction and fractionation procedure covering a broad spectrum of lipophilic (e.g., fatty acid methyl esters, hydrocarbons, fatty alcohols, sterols) and hydrophilic (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 35 publications
14
104
1
2
Order By: Relevance
“…The growth of seeds is accompanied by monocotyledonous morphological developments involving the initial enlargement of the rice embryos and the subsequent formations of shoots and roots. This phenomenon is in agreement with the germination progress previously described for brown rice (Shu et al 2008). The developmental changes upon sprouting process of non-colored, red, purple, and black Thai indica rice samples were comparable.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The growth of seeds is accompanied by monocotyledonous morphological developments involving the initial enlargement of the rice embryos and the subsequent formations of shoots and roots. This phenomenon is in agreement with the germination progress previously described for brown rice (Shu et al 2008). The developmental changes upon sprouting process of non-colored, red, purple, and black Thai indica rice samples were comparable.…”
Section: Resultssupporting
confidence: 92%
“…GC-based metabolite profiling techniques were also applied to follow the natural development of plant-derived food, for example, the metabolic changes in the course of germination of rice (Shu et al 2008), potato , barley and mung beans (Na Jom et al 2011), among which germinated rice has commonly received great attention (Wu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the agricultural importance of cereal grains, previous metabolomics-based work has focused on these processes during the germination of rice (Oryza sativa; Shu et al, 2008) and the malting process for barley (Hordeum vulgare;Frank et al, 2011). However, traditional metabolomics analyses often prove laborious and challenging, with limited spatial information.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the metabolic pathways that are induced during the seed germination processes that involve starch, oil, and protein turnover have been studied via molecular, genetic, and biochemical studies (Ingle et al, 1964;Limami et al, 2002;Shu et al, 2008;Zhang et al, 2009). Therefore, techniques that allow for the determination of the spatial localization of metabolites in fine detail, specifically mass spectrometry imaging (MSI), should allow for further insight into the mechanisms and actions of the pathways that are integral to seed germination.…”
mentioning
confidence: 99%
“…7À9 As a useful metabolic tool, GC-MS coupled with multivariate analysis was widely used in nontargeted tests of metabolites in different rice germplasms. 10,11 However, no study has reported an investigation of the metabolic diversity in a large germplasm set and linked metabolite contents with DNA markers by association mapping.…”
Section: ' Introductionmentioning
confidence: 99%